PENURUNAN DEFECT CACAT TENUN IKAT DENGAN DMAIC SIXSIGMA PADA CV. PARADILA LAMONGAN - Setiawan, Gagok (Teknik Kimia ITN Malang, 2023)
Efforts to reduce product defects on cloth fabrics in CV. Paradila Lamongan have been made but not maximized, resulting in the price can not be high so the profit is reduced. Through the inspection process at the end of production often found defects of the product which resulted in the price of bandage fabric falling because it did not meet consumer standards. Evaluation is required on each production line to obtain data on the cause of the defect of the cloth. The DMAIC Six Sigma method notes that there are three most common causes of defects: Lusi jump, Faulty feeding and Empty eating. Especially for the lusi jump has a presentation of 62.8% as the biggest cause of product defects. Datasheet recording in September 2023 reached 29 meters. With measure and analyze of DMAIC then made datas some improvement in solving problems is the most important improvement skill and knowledge of machine operators in running SOP and maintenance.